2019
DOI: 10.1016/j.athoracsur.2018.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Cardio-omentopexy Reduces Cardiac Fibrosis and Heart Failure After Experimental Pressure Overload

Abstract: Background.-The pedicled greater omentum has been shown to offer benefit in ischemic heart disease for both animal models and human patients. The impact of cardio-omentopexy in a pressure overload model of left ventricular hypertrophy (LVH) is unknown. Methods.-LVH was created in rats by banding the ascending aorta after right thoracotomy (n = 23). Sham surgery was performed in 12 additional rats. Six weeks after banding, surviving LVH rats were assigned to cardio-omentopexy by left thoracotomy (LVH + Om, n =8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Nevertheless, it is important to stress that the new murine cardioprotective COP phenotype is consistent with our previously reported COP-mediated cardioprotection in rats. 10 This indicates a reproducible consistency in rodents and that the therapeutic potential of COP is conserved between species. The generation of the murine COP model is the first step in leveraging the array of experimental tools in the mouse to understand COP cardioprotection at the molecular level.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Nevertheless, it is important to stress that the new murine cardioprotective COP phenotype is consistent with our previously reported COP-mediated cardioprotection in rats. 10 This indicates a reproducible consistency in rodents and that the therapeutic potential of COP is conserved between species. The generation of the murine COP model is the first step in leveraging the array of experimental tools in the mouse to understand COP cardioprotection at the molecular level.…”
Section: Discussionmentioning
confidence: 80%
“…9 Recently, a study from our laboratory showed that COP ameliorated left ventricular hypertrophy and dysfunction in a rat model of pressure overload. 10 The underlying mechanisms of action remain unclear. This investigation first confirms that COP has angiogenic and cardioprotective roles in a murine model of pressure overload (Video 1).…”
Section: Perspectivementioning
confidence: 99%